(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2020)
This work was carried out during two seasons 2017,2018 on 30 years old trees of olive orchard in ALkhalouf area of Lattakia Governorate on khodeiry variety, with the aim of studying the effect of foliar spraying with boron, zinc and humic acid on yield, oil percentage, fruit and seeds characteristics of khodeiry variety. These nutrients were sprayed singly or incombination on olive trees three times during the growing season in the following concentrations: boron 200 ppm, zinc 75 ppm and humic acid 250ppm. Before flowering, after fruit setting and afte fruit weight, seed weight, pulp weight, fruit size ,seed size, production quantity and oil percentage were calculated. The statistical analysis of the results, showed a significant increase of all productive indicators compared to the control. The treatment (HA+Zn+B) showed a significant increase in yield 46.75kg/tree, while it didn’t exceed 28.33kg/tree for the control. The percentage of oil in the said treatment was 28.85%, while it was only 25.06% in the control as an average for the two seasons mentioned. The treatments of foliar application singly or incombination recorded a significant increase in oil percentage. The results of the statistical analysis showed a significant increase of weights of the fruits and seeds and average of pulp weight and pulp/fruit weight ratio. While control treatment recorded the minimum value in all studied treatments. نُفذت التجربة خلال موسمي (2017 و 2018) على أشجار زيتون صنف "الخضيري" بعمر 30 عام في منطقة القلوف التابعة لمحافظة اللاذقية، بهدف دراسة تأثير التغذية الورقية بعنصري البورون والزنك وحمض الهيومك في إنتاج أشجار الزيتون صنف "الخضيري"، ونسبة الزيت ومواصفات الثمار والنوى. رشت هذه العناصر بشكل منفرد أو على شكل خليط في ثلاث مواعيد: قبل الإزهار، وبعد العقد، وبعد25 يوم من الرشة الثانية؛ إذ رشت بحمض الهيومك تركيز 250ppm، والبورون200ppm، والزنك75ppm. تم قطاف المحصول في نهاية شهر تشرين الأول. تم حساب متوسط وزن الثمرة، وزن النواة، وزن اللب، ونسبة التصافي، كما حُسب متوسط حجم الثمرة، وحجم النواة، وكمية الإنتاج، ونسبة الزيت. لُوحظ من خلال نتائج التحليل الإحصائي تفوق معاملة التغذية الورقية بـــ (هيومك250ppm + 75 ppmZn + 200 ppmB) معنوياً في جميع المؤشرات المدروسة مقارنة بالشاهد؛ إذ بلغ متوسط إنتاج الشجرة 46.75 كغ، بينما لم يتعد 28.33كغ في الشاهد. وبلغت نسبة الزيت في المعاملة المذكورة 28.85%، بينما لم تتعد 25.06% في الشاهد كمتوسط للموسمين المذكورين. كما حققت معاملات التغذية الورقية بالعناصر المذكورة سواء استخدمت مفردة أو على شكل خلائط منها زيادة معنوية في المؤشرات المدروسة وتفوقت معنوياً على الشاهد.